(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2019)
As both the value of educational assessment for educational development and peace education for social development are increasingly recognised, it is of concern that peace education has as of yet no widely accepted assessment methodology. This may be due to the absence of agreed learning objectives. Instead, peace education programmes tend to be evaluated as interventions to directly achieve peace, bypassing the need for learning outcomes. Using Delphi methodology, this study enquired how we could arrive at learning outcomes for peace education. This instance of Delphi was organised with a group of 16 experts in peace education. This Delphi found a difference between the social purpose of peace education and its learning outcomes. While its social purpose is peace, to be education, it must have learning objectives. While peace education is understood as education on group identity and diversity, this can be engaged with cognitively and non-cognitively, suggesting different types of outcomes. The Delphi concluded that learning outcomes in peace education culminate in inter-cultural communication skills, combining cognitive with non-cognitive characteristics. The offered understandings are underpinned by a relational conception of peace that is open-ended and non-utopian.